How, why, where and when people feed birds?—Spatio‐temporal changes in bird‐feeding in Finland - Purabi Deshpande; Anna Haukka; Katja Rönkä; Tuomas Aivelo; Andrea Santangeli; Rose Thorogood; Aleksi Lehikoinen (People and Nature)
Abstract Providing food to animals, especially birds, during winter is a common activity in many countries. While bird‐feeding can increase connections between people and nature, there are increasing calls from researchers and the general public to limit this activity due to emerging knowledge of potential negative ecological impacts (e.g. biased competition and spread of pathogens). However, what motivates changes in bird‐feeding habits remains largely unknown, despite the ‘provisioners’ perspective’ being critical for designing and implementing policy that benefits both animals and people. Here, we investigate changes in how and why people feed birds in urban and rural areas of Finland as a case study. We made use of two long‐term annual bird monitoring data sets (the Winter bird census and Finnish bird feeder monitoring scheme) to investigate how the number of bird‐feeding sites and the amount of food provisioned have changed since the 1980s. Additionally, we conducted an online questionnaire in 2021 (over 14,000 respondents) to examine reasons for the changes that we detected. We find that, over 40 years, the annual amount of food provided has increased significantly in rural areas, while the number of bird‐feeding sites has decreased and especially so in urban areas. Questionnaire answers indicated that this decline was likely due to changing regulations of local governments and housing organisations, with increased concerns of attracting pests leading to restrictions on providing food for birds. In rural areas, people who reduced feeding more often identified concerns over avian diseases and the effort required to access, clean and refill bird‐feeding sites. Policy implications: Our results highlight that provisioning food to wild animals involves complex decision‐making depending on habitat, geography and economic factors. Therefore, policies designed to curb (or promote) this activity should take into account its multifaceted nature. Read the free Plain Language Summary for this article on the Journal blog.